Synergistic Effect of 3',4'-Dihidroxifenilglicol and Hydroxytyrosol on Oxidative and Nitrosative Stress and Some Cardiovascular Biomarkers in an Experimental Model of Type 1 Diabetes Mellitus - José Pedro De La Cruz Cortés; Leticia Vallejo-Carmona; María Monsalud Arrebola; Esther Martín-Aurioles; María Dolores Rodriguez-Pérez; Laura Ortega-Hombrados; Cristina Verdugo; María África Fernández-Prior; Alejandra Bermúdez-Oria; José Antonio González-Correa (MDPI AG, 2021)
The objective of this study was to assess a possible synergistic effect of two extra-virgin olive oil polyphenols, 3,4,-dyhydroxyphenylglycol (DHPG) and hydroxytyrosol (HT), in an experimental model of type 1 diabetes. Seven groups of animals were studied: (1) Nondiabetic rats (NDR), (2) 2-month-old diabetic rats (DR), (3) DR treated with 5 mg/kg/day p.o. HT, (4) DR treated with 0.5 mg/kg/day p.o. DHPG, (5) DR treated with 1 mg/kg/day p.o. DHPG, (6) DR treated with HT + DHPG (0.5), (7) DR treated with HT + DHPG (1). Oxidative stress variables (lipid peroxidation, glutathione, total antioxidant activity, 8-isoprostanes, 8-hydroxy-2-deoxyguanosine, and oxidized LDL), nitrosative stress (3-nitrotyrosine), and some cardiovascular biomarkers (platelet aggregation, thromboxane B2, prostacyclin, myeloperoxidase, and vascular cell adhesion protein 1 (VCAM-1)) were analyzed. The diabetic animals showed an imbalance in all of the analyzed variables. HT exerted an antioxidant and downregulatory effect on prothrombotic biomarkers while reducing the fall of prostacyclin. DHPG presented a similar, but quantitatively lower, profile. HT plus DHPG showed a synergistic effect in the reduction of oxidative and nitrosative stress, platelet aggregation, production of prostacyclin, myeloperoxidase, and VCAM-1. This synergism could be important for the development of functional oils enriched in these two polyphenols in the proportion used in this study.